2010
DOI: 10.1080/09658210903476514
|View full text |Cite
|
Sign up to set email alerts
|

Valence and the development of immediate and long-term false memory illusions

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. and children's (Experiment 2) true recall and recognition was better for neutral than negative items and although false recall was also higher for neutral items, false recognition was higher for negative items. The last three experiments examined adults' (Experiment 3) and children's (Experiments 4 and 5) one-week long-term recognition of neutral and negative-emotional information. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
153
5
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 126 publications
(186 citation statements)
references
References 55 publications
26
153
5
2
Order By: Relevance
“…Previous research has found that reversal effects emerge independent of the emotional nature of stimuli (Brainerd, Holliday, Reyna, Yang, & Toglia, 2010;Howe, Candel, Otgaar, & Malone, 2010). However, most of this research has focused exclusively on emotion and developmental reversal effects in spontaneous false memories.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has found that reversal effects emerge independent of the emotional nature of stimuli (Brainerd, Holliday, Reyna, Yang, & Toglia, 2010;Howe, Candel, Otgaar, & Malone, 2010). However, most of this research has focused exclusively on emotion and developmental reversal effects in spontaneous false memories.…”
Section: Discussionmentioning
confidence: 99%
“…Four DRM lists (2 neutral: bread, foot; 2 negative: pain, cry) were drawn from a larger pool (see Howe et al, 2010) "'Big' Bertha was the daughter of the baker. Her name was actually just Bertha, but because she loved butter and sweet fillings, she became a bit bigger in weight.…”
Section: Materials and Proceduresmentioning
confidence: 99%
“…The effectiveness of these lists in eliciting spontaneous false memories has already been demonstrated in previous research (Howe et al, 2010;Otgaar & Candel, 2011;Otgaar et al, 2012b). List items were chosen from the Dutch word association norms (Van Loon-Vervoorn & Van Bekkum, 1991) and were presented in order of backward associative strength, from strongest to weakest, in line with Howe et al (2010) and Otgaar and Candel (2011). With assistance of the CELEX lexical database (Baayen, Piepenbrock, & Gulikers, 1995), we made sure that the mean word frequency of the neutral and emotional critical lures did not differ, t(8) = 0.22, ns.…”
Section: Methodsmentioning
confidence: 94%
“…We used 5 neutral (bread, window, sweet, smoke, feet) and 5 negative (murder, pain, punishment, death, cry) DRM word lists with each list containing 10 words. The effectiveness of these lists in eliciting spontaneous false memories has already been demonstrated in previous research (Howe et al, 2010;Otgaar & Candel, 2011;Otgaar et al, 2012b). List items were chosen from the Dutch word association norms (Van Loon-Vervoorn & Van Bekkum, 1991) and were presented in order of backward associative strength, from strongest to weakest, in line with Howe et al (2010) and Otgaar and Candel (2011).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation